THE CHALLENGES FACED BY GERIATRIC NURSES LONG-TERMCAREFACILITIES - Alanoud Humaidi Rakyan Alanazi, Nasser Saad Hamed Aldossary, Mohammed OmarAbdullah Al Dhirgham, Noura Tawersh Al Onezi, Faisal Marqhal Thani Alanazi, Hind Yahya Hadadi, Fadhel Mesfer Alkhathami, Muneefaa Marzouq Alenezi, Ahmed Hussain Sufyani; Hamdan Alaife Alonazi, Saud Mokhlif Alanze, Riyadh Abdullah Al Zahrani, Aljoharah Zaid Binnamshan,Aljoharah Zaid Binnamshan, Ali Mohammed Ali Haqwi (Chelonian Research Foundation, 2022)
A comprehensive assessment of qualitative evidence on nurses' self-descriptions of their end-of-life care practice has not been conducted. The objective is to compile qualitative informationabouttheend-of-lifecarepracticesofnursesinlong-termcaresettingsforolderpersons.Published and unpublished research in English were searched for in the databases MEDLINE,CINAHL,PsycINFO,EMBASE,Mednar,GoogleScholar,andIchushi.Their137findingswerecategorizedinto10distinctconclusions:assumingdiverseroupsandsubsequentlycombinedintothreesynthesizedrolestofacilitatethedignifiedpassingofresidents,requiring resourcesandsupporttomaintainprofessionaldedication,andexperiencingadiscrepancybetween responsibilities and authority, which impacts multidisciplinary collaboration. Nursesfulfill multifaceted duties as the healthcare providers with the greatest expertise in addressing theintricate demands of residents. Managers and politicians should provide nurses the authority toaddress the discrepancy and assist them in acquiring the necessary resources for end-of-life care,therebyensuringthatresidentspassawaywithdignity. Keywords:end-of-life(EOL)interventions. care, elderly patients, review, geriatric nurses, nursing